Distinct small RNAs are expressed at different stages of Phytophthora capsici and play important roles in development and pathogenesis - Zhong, Shan; Zhang, Sicong; Zheng, Yang; Zhang, Qinghua; Liu, Fangmin; Wang, Zhiwen; Liu, Xili (Frontiers in Genetics, 2024)
Small RNAs (sRNAs) are important non-coding RNA regulators that play key roles in the development and pathogenesis of plant pathogens, as well as in other biological processes. However, whether these abundant and varying sRNAs are involved in Phytophthora development or infection remains enigmatic. In this study, sRNA sequencing of 4 asexual stages of Phytophthora capsici (P. capsici), namely, as mycelia (HY), sporangia (SP), zoospores (ZO), cysts (CY), and pepper infected with P. capsici (IN), were performed, followed by sRNA analysis, microRNA (miRNA) identification, and miRNA target prediction. sRNAs were mainly distributed at 25–26 nt in HY, SP, and ZO but distributed at 18–34 nt in CY and IN. 92, 42, 176, 39, and 148 known miRNAs and 15, 19, 54, 13, and 1 novel miRNA were identified in HY, SP, ZO, CY, and IN, respectively. It was found that the expression profiles of known miRNAs vary greatly at different stages and could be divided into 4 categories. Novel miRNAs mostly belong to part I. Gene ontology (GO) analysis of known miRNA-targeting genes showed that they are involved in the catalytic activity pathway, binding function, and other biological processes. Kyoto Encyclopedia of Gene and Genome (KEGG) analysis of novel miRNA-targeting genes showed that they are involved in the lysine degradation pathway. The expression of candidate miRNAs was validated using quantitative reverse transcription–polymerase chain reaction (qRT–PCR), and miRNAs were downregulated in PcDCL1 or PcAGO1 mutants. To further explore the function of the detected miRNAs, the precursor of a novel miRNA, miR91, was knockout by CRISPR-Cas9, the mutants displayed decreased mycelial growth, sporangia production, and zoospore production. It was found that 503142 (Inositol polyphosphate 5-phosphatase and related proteins) can be predicted as a target of miR91, and the interaction between miR91 and 503142 was verified using the tobacco transient expression system. Overall, our results indicate that the diverse and differentially expressed sRNAs are involved in the development and pathogenesis of P. capsici.